Comparison of Medan State University Students' Preferences for Online Motorcycle Taxi Platforms: A Case Study on GOJEK and GRAB - Fitri, Anisa; Nasution, Mutiara Akbar; Utami, Ananda Putri; Toruan, Anjel Monika Lomban; Panjaitan, Bonjovi Marselino (Lembaga Riset Mutiara Akbar (LARISMA), 2023)
This study was conducted with the aim of determining the preferences of Medan State University students between the Grab and Gojek online motorcycle taxi platforms. This study uses a qualitative method where the author collects respondent data through a questionnaire. The qualitative method is used for the reason of measuring the comparison of online motorcycle taxi platforms used by students of Medan State University (UNIMED). The results of this study indicate that the preferences of Medan State University students vary between Grab and Gojek due to several factors that influence them. From the results of this study, it can be seen that the preferences of Medan State University students tend to choose Grab. Grab is considered to offer more attractive discounts and promos and cheaper prices. Meanwhile, some students choose Grab because it offers a wider variety of payment methods. From this study, we can see that the promotion factor is the thing that most influences student preferences at UNIMED. From both of these platforms, they have positive experiences and satisfaction from consumers and students are willing to recommend Grab and Gojek as online motorcycle taxi platforms to others.